A novel robust frequency-constrained unit commitment model with emergency control of HVDC. (November 2022) - Jiang, Sufan; Zhao, Xin; Pan, Guangsheng; Gao, Shan; Wu, Chuanshen; Liu, Yu; Wang, Sicheng
Abstract: High-voltage direct current (HVDC) transmission systems are widely employed to transmit energy among systems with renewable energy integrated. However, the reduced system inertia and the risk of HVDC failure pose significant challenges to operators. To ensure system reliability especially frequency stability under extreme circumstances, a robust frequency-constrained unit commitment (FCUC) model is proposed in this paper. Unlike previous studies, an extra power-rescheduling procedure is embedded in our model, and consequently the FCUC model is formulated as a three-layer structure, where the day-ahead schedule model, emergency corrective model (primary frequency response), and power rescheduling (secondary frequency response) are co-optimized. Accordingly, an improved tri-level Benders Decomposition (BD) algorithm was developed to solve the problem. By leveraging the optimality cuts of the algorithm, the characteristics of fast power support and flexible regulation capabilities of HVDC system in real-time (RT) market are preemptively considered in DA market. Consequently, the model feasible region is more adaptive to the plausible contingencies The outperformance of our model was validated by the numerical experiments in an asynchronous HVDC interconnected system. The results demonstrate that by formulating the coordination of AC–DC dispatch framework, the global optimal operational cost is further captured when ensuring the system reliability.